Indonesia's Interests in the Pacific Region - Buiney, Mariana Erny; Wambrauw, Meyland Sabinna Fenescha (PT FORMOSA CENDEKIA GLOBAL, 2024)
Indonesia is a country that is located close to each other and has established diplomatic relations and cooperation with countries in the Pacific region. This is done to maintain national and regional stability. Indonesia has an interest in maintaining a stable, prosperous and friendly environment in the Pacific region. On the other hand, Pacific countries view Indonesia as an archipelagic country that has experience and capacity in terms of cooperation and development. This research aims to analyze Indonesia's interests in countries in the Pacific Region. These interests include: strengthening sovereignty, increasing economic & trade cooperation and partners supporting each other in regional and multilateral forums. The research results show that the dynamics of Indonesia's cooperation with countries in the Pacific region have gone well in recent years. Indonesia carries out a lot of cooperation in the form of training and capacity development for Pacific countries. Apart from that, Indonesia is also active in organizing activities and discussion forums to encourage increased relations and cooperation